Iodine deficiency in Israeli pregnant women - a time for action - John H. Lazarus (BMC, 2020)
Abstract Iodine is an essential micronutrient for thyroid gland function. Iodine deficiency disorders are a spectrum of conditions affecting the fetus, child, adolescent and adult. Iodine requirements are increased in pregnancy in order that the fetus receives enough maternal thyroxine via transplacental passage. Previous studies in Israel have shown widespread iodine deficiency by measurement of urinary iodine concentrations in school age children and adults. The present study clearly shows iodine deficiency in a group of 2nd trimester women as judged by measurement of serum thyroglobulin (a recently evaluated marker of iodine deficiency). An additional factor in this work is that the subjects all resided in an area using desalinated water. Desalination has previously been shown to significantly reduce the iodine content of water compared to water in Israel not subject to this process. The data in this group of pregnant women should serve as a wakeup call to the public health community to correct this deficiency which is known to significantly affect child neurodevelopment. There are several issues to be addressed. The knowledge base relating to iodine nutrition especially during pregnancy is low. An educational plan is required. The strategy for achieving adequate iodine nutrition in the population and particularly before and during pregnancy requires urgent review. While iodine supplementation before and during gestation can correct iodine deficiency, the provision of iodised salt in the community is recommended, similar to more than 80% of countries in the world. It is indeed a time for action to ensure the adequate intellectual performance of Israel's children.